If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = n + (-7) -18 = n + -7 Reorder the terms: -18 = -7 + n Solving -18 = -7 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -18 + -1n = -7 + n + -1n Combine like terms: n + -1n = 0 -18 + -1n = -7 + 0 -18 + -1n = -7 Add '18' to each side of the equation. -18 + 18 + -1n = -7 + 18 Combine like terms: -18 + 18 = 0 0 + -1n = -7 + 18 -1n = -7 + 18 Combine like terms: -7 + 18 = 11 -1n = 11 Divide each side by '-1'. n = -11 Simplifying n = -11
| C=2(pi)2 | | (3x^2/2)=4 | | (125)^-2/3 | | 0.5^1/5 | | 2/3+3m/13=8/13 | | -21=m+16 | | 33x^2+50x+8= | | (-1/9x^-4y^5z^-1)(-12x^-3y^-1z^4) | | 2=5y-8x | | -i=20 | | 49r^2-25f^2= | | 3/4(8x-4)+3=2/5(5x+10)-1 | | 13=t-10 | | (-4/9)(-9/12) | | 3y+4+4+5y=-6 | | 3x+5+2x-1=x+11 | | 25+7x=8x+15 | | 8x+11+12-1=180 | | 3x^2+1=13 | | 81b^3-16b=0 | | 2(a-5)-(4a+4)=5(4a+2)-2 | | 12j-7=5 | | 6x=54+3x | | -1--2= | | 3x-6=t-2 | | 4(x/2-1)-1/8(3-2x)=0 | | c-19=-33 | | -3/2x=14 | | -7(x-5)=-21+7x | | 4+2e=16 | | 6(2b+1)=-4-3(-4b+2) | | -1x=7x+2 |